(untitled) (Research, Society and Development, 2022)
Introduction: The cardiovascular diseases (CVD) are considered the leading cause of death in the world, being considered a public health problem, the concern increases as currently the number of deaths in younger individuals and in vulnerable groups. The aim of the study was to determine the association between the level of education and premature death from cardiovascular diseases in adults. Methodology: This is a cross-sectional study of analytical nature, resulting from data from the Mortality Information System of Brazil in 2018. For statistical analysis, a bivariate analysis was performed using the chi-square test and later a multivariate analysis was performed using a logistic regression model to control for confounding and modifying factors, adjusting the proportional mortality ratio (PRM) values. Result: 452,282 deaths were analyzed; 16.7% of which were attributed to cardiovascular diseases, regarding the level of education, a higher prevalence of death from CVD diseases (17.3%) was observed in illiterate or with primary schools’ education and male (62.8%). After full adjustment for possible confounding factors, illiteracy or having only elementary education remained strongly associated with the risk of dying prematurely from CVD (RMP =1.31; 95% CI 1.27-1.24, p<0.000). Gender interacted with education level: where female subjects (RMP=1.30, 95% CI1.27-1.35). Conclusion: The mortality rate from cardiovascular disease is high among poorly educated people, suggesting a multisectoral approach (access to education and health) targeting vulnerable people.